Efektivitas Sayur Pakis Terhadap Kadar Hb Pada Ibu Hamildi Wilayah Kerja Puskesmas Cempaka Kabupaten Purwakarta - Hekmawati, Shanti; Awekawati, Wiwi (Jurnal Sosial Teknologi, 2025)
Anemia is a health problem around the world, including developing countries where it is estimated that 30% of the world's population suffers from anemia. The problem of low Hb levels that trigger anemia affects 56 million women, and as many as two-thirds of them are from Asia. Ministry of Health of the Republic of Indonesia (2015) Nutritional anemia currently still needs special attention in Indonesia. Riskesdas data in 2013 shows that the problem of anemia in pregnant women reaches 37.1%. The prevalence in 15-year-old women is 22.7%. In South Kalimantan Province the percentage of anemia of pregnant women in South Kalimantan province is 21.17 (2019), the percentage of anemia of pregnant women in South Kalimantan Province has decreased to 20.13% (2020) Anemia is a medical condition with hemoglobin (Hb) levels, hematocrit values and the number of erythrocytes in the body less than the normal limit so that it cannot fulfill its function to provide oxygen for all body tissues. Lack of knowledge about the source of iron intake triggers anemia, the most common one found in Indonesia is iron deficiency anemia (Bambang, 2012). Iron deficiency anemia more often affects pregnant women, this is because during pregnancy the need for iron increases. Pregnant women who experience bleeding during childbirth can also cause more iron loss (Soebroto, 2020). Pregnancy tends to be identical to low Hb levels. To Determine the Effectiveness of Fern Vegetables on Hemoglobin Levels in Pregnant Women in the working area of the Cempaka Health Center, Purwakarta Regency. The research is quasi-experimental type one pretest and posttest group. The population of all pregnant women was 31 people, with purposive sampling techniques for inclusion criteria and exclusion of 31 people. The instrument used is an observation sheet. Based on the sapphiro wilk test, the data is normally distributed, the test used is paired sample test. Bivariate analysis was the average Hb pretest level of 11.70 ± SD 1.25, the average Hb posttest level was 11.81 ± SD 1.16. Results of the Hypothesis test p-value = 0.357 (p>0.05).